An integrated-molecular-beacon based multiple exponential strand displacement amplification strategy for ultrasensitive detection of DNA methyltransferase activity - Cui, Yun-Xi; Feng, Xue-Nan; Wang, Ya-Xin; Pan, Hui-Yu; Pan, Hua; Kong, De-Ming (Chemical science (Cambridge), 2019)
DNA methylation is a significant epigenetic mechanism involving processes of transferring a methyl group onto cytosine or adenine. Such DNA modification catalyzed by methyltransferase (MTase) plays important roles in the modulation of gene expression and other cellular activities. Herein, we develop a simple and sensitive biosensing platform for the detection of DNA MTase activity by using only two oligonucleotides. The fluorophore labeled molecular beacon (MB) can be methylated by MTase and subsequently cleaved by endonuclease DpnI at the stem, giving a shortened MB. The shortened MB can then hybridize with a primer DNA, initiating a cycle of strand displacement amplification (SDA) reactions. The obtained SDA products can unfold new MB and initiate another cycle of SDA reaction. Therefore, continuous enlargement of SDA and exponential amplification of the fluorescence signal are achieved. Because the triple functions of substrate, template and probe are elegantly integrated in one oligonucleotide, only two oligonucleotides are necessary for multiple amplification cycles, which not only reduces the complexity of the system, but also overcomes the laborious and cumbersome operation that is always a challenge in conventional methods. This platform exhibits an extremely low limit of detection of 3.3 × 10 −6 U mL −1 , which is the lowest to our knowledge. The proposed MTase-sensing platform was also demonstrated to perform well in a real-time monitoring mode, which can achieve a further simplified and high-throughput detection. The sensing strategy might be extended to the activity detection of other enzymes, thus showing great application potential in bioanalysis and clinical diagnosis.